An unusual case of primary melioidotic prostatic abscess complicated by perianal abscess. (2018) - Chee, Y.C.; Chee, Y.N.
Abstract: Burkholderia pseudomallei is recognized to cause severe and fatal infections. Most of the infections caused by this facultative intracellular gram-negative bacterium are pneumonia, soft tissue, genito-urinary and central nervous system infection. We report an unusual case of primary prostatic abscess complicated by perianal abscess caused by Burkholderia pseudomallei . Melioidosis related anorectal infections have not been previously reported in the literature.